EMPOWERING COASTAL COMMUNITIES BY DEVELOPING PROCESSED FISH PRODUCTS INNOVATIVE BASED ON LOCAL POTENTIAL IN BUNGKUTOKO SUB-DISTRICT, KENDARI CITY - Jafriati, Jafriati; Salsabila, Syefira; Hadi, Arie Toursino; Nurmaladewi, Nurmaladewi; Akifah, Akifah; Al Mahmud, Nabil; Pratiwi, Putri Awalinda; Yasrul, Yasrul; Maliany, Nur Satya; Putry, Gigih Dwiandiny Purwanto (LPPM Univ. Ibn Khaldun Bogor, 2026)
This empowerment program aims to strengthen the capacities of coastal women in Bungkutoko Subdistrict through the development of innovative fish-based products using local potential. The situational analysis indicated limited diversification of processed fish products, low digital marketing skills, and weak household economic resilience. The program addressed these needs through training on processing fish into Abon WaPesisir with various flavors, nutrition education, the use of appropriate technology (fish floss mixer, vacuum sealer, standing pouches), preparation of production SOPs, branding enhancement, and digital marketing training using social media and online marketplaces. In addition, the activities integrated the strengthening of women's roles through mentoring, group learning, and entrepreneurial soft‑skills development. The results showed increases in participants' knowledge, production skills, food hygiene practices, and digital marketing capabilities. The group succeeded in producing more than 50 packages of ready‑to‑sell fish floss with more consistent quality, modern packaging design, and the “Abon WaPesisir” brand. Participants were also able to create promotional content, manage social media accounts, and begin expanding their marketing networks. Overall, the program had positive impacts, including enhanced self‑confidence, strengthened business capacity, and greater opportunities to improve household income among coastal families.